Preparation method and application of defect-rich cobalt-aluminum hydrotalcite loaded noble metal catalyst

By growing cobalt-aluminum hydrotalcite precursor on foam nickel substrate and creating metal defect positions through alkali etching, uniform anchoring of precious metals is achieved, solving the problem of low load efficiency in the existing precious metal-loaded cobalt-based hydrotalcite catalyst preparation method. , the catalytic efficiency and electrochemical active area of ​​the catalyst are improved.

CN119465264APending Publication Date: 2025-02-18JIANGSU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411591356.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing preparation methods for the precious metal-supported cobalt-based hydrotalcite catalyst have problems such as slow ion exchange rate and high ion requirements in the support, which limits the loading efficiency and catalytic activity of precious metals.

Method used

Defectively rich cobalt-aluminum hydrotalcite loads are constructed by growing cobalt-aluminum hydrotalcite precursors by hydrothermal reaction on foamed nickel substrates and creating metal defective sites by alkali etching treatment, followed by uniform anchoring of precious metals at these sites, thereby building defect-rich cobalt-aluminum hydrotalcite loads Precious metal catalyst.

Benefits of technology

The catalytic efficiency and electrochemical active area of ​​the catalyst are improved, the energy consumption of hydrogen production by electrolyzing water is reduced, the production process is simplified, and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465264A_ABST
    Figure CN119465264A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a cobalt-aluminum hydrotalcite loaded noble metal catalyst rich in metal defects. The preparation method comprises the following steps: dissolving a cobalt source, an aluminum source, urea and ammonium fluoride in an aqueous solution, and carrying out hydrothermal reaction to obtain a cobalt-aluminum hydrotalcite precursor; the preparation method comprises the following steps: preparing a precursor, treating the precursor with an alkaline solution to obtain a defect-rich cobalt-aluminum hydrotalcite carrier, and dipping the defect-rich cobalt-aluminum hydrotalcite carrier in a noble metal solution to obtain the defect-rich cobalt-aluminum hydrotalcite supported noble metal catalyst. The preparation method is simple and high in operability, the noble metal can be anchored on the defect-rich cobalt-aluminum hydrotalcite carrier, and the defect-rich cobalt-aluminum hydrotalcite loaded noble metal catalyst can be used as a bifunctional catalyst through the synergistic effect of the noble metal and the cobalt-aluminum hydrotalcite carrier, has excellent electro-catalytic performance, and can be used for preparing a catalyst for preparing the cobalt-aluminum hydrotalcite loaded noble metal catalyst with the defect-rich cobalt-aluminum hydrotalcite loaded noble metal catalyst with the defect-rich cobalt-aluminum hydrotalcite loaded noble metal catalyst. And the electrolytic tank assembly process is simplified, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrocatalyst preparation, and specifically relates to a preparation method and application of a defect-rich cobalt-aluminum hydrotalcite-loaded noble metal catalyst. Background Art

[0002] Energy and environment are the most important issues in the sustainable development of human society. Excessive use of fossil fuels will lead to serious environmental pollution. Hydrogen has the characteristics of high energy density, high utilization efficiency and environmental friendliness. It is an ideal renewable energy source and can be used as a substitute for traditional fossil fuels. In recent years, the electrolysis of water to produce hydrogen technology can achieve large-scale, low-cost hydrogen production and has no carbon emissions in the production process, which has attracted more and more attention. Its hydrogen production accounts for 4% of the global total hydrogen production. At present, precious metal platinum (Pt) and its alloy materials are still the most efficient hydrogen evolution catalysts, and ruthenium oxide materials are considered to be efficient oxygen evolution catalysts, but problems such as high cost, low reservoir abundance and poor stability have greatly limited their commercial application. Therefore, it is necessary to develop efficient and relatively abundant non- / low-content precious metal electrocatalysts to replace platinum-based materials.

[0003] In recent years, cobalt-based hydrotalcite materials have been used to study the field of hydrogen evolution and oxygen evolution electrocatalysis, but the catalytic effect of hydrogen evolution of cobalt-based hydrotalcite is not ideal, mainly because the hydrotalcite has poor adsorption and desorption ability for hydrogen, resulting in low hydrogen evolution catalytic activity. In order to improve the intrinsic catalytic activity of cobalt-based hydrotalcite, currently commonly used methods include heteroatom doping, heterostructure construction, defect engineering, and precious metal loading to optimize the electronic structure of cobalt-based hydrotalcite, thereby improving its intrinsic catalytic activity. Among them, precious metal loading has a more obvious performance improvement for cobalt-based hydrotalcite compared with other methods, but currently precious metal loading is usually carried out by ion exchange method, which has high requirements for the ions contained in the carrier, and the ion exchange rate is slow, which greatly limits the effective loading efficiency of precious metals. In view of this, the method for preparing efficient and stable precious metal-loaded cobalt-based hydrotalcite materials is very scarce. At this stage, it is urgent to develop a simple and efficient method to construct highly active precious metal-loaded cobalt-based hydrotalcite materials. Summary of the invention

[0004] In order to overcome the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing and applying a defect-rich cobalt-aluminum hydrotalcite-loaded precious metal catalyst, and to utilize a method for rapidly anchoring precious metals at metal defect vacancies in cobalt-aluminum hydrotalcite to regulate the precious metal loading, optimize the electronic structure, and improve the catalytic efficiency of the catalyst.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing a defect-rich cobalt-aluminum hydrotalcite-supported noble metal catalyst, comprising the following steps:

[0007] (1) pre-treating the nickel foam to remove the oxide on its surface, and then placing the pre-treated nickel foam in a mixed solution containing a certain proportion of a cobalt source, an aluminum source, ammonium fluoride, urea and water, and growing a cobalt aluminum hydrotalcite precursor on the nickel foam substrate through a hydrothermal reaction;

[0008] (2) further treating the cobalt aluminum hydrotalcite precursor obtained in step (1) with alkali etching and then drying to obtain a defect-rich cobalt aluminum hydrotalcite carrier;

[0009] (3) Immersing the defect-rich cobalt aluminum hydrotalcite precursor obtained in step (2) into a noble metal solution, taking out the sample after the immersion is completed and drying it, and finally obtaining the defect-rich cobalt aluminum hydrotalcite-loaded noble metal catalyst.

[0010] In step (1), the nickel foam pretreatment process is as follows: first, the nickel foam is cut into (1-3)×(1-3) cm 2 Size, preferably 2.5 x 3 cm 2 Then, the nickel foam was ultrasonically cleaned in an acidic solution with a pH value less than 4, anhydrous ethanol and deionized water for 5 minutes to remove the oxide on its surface, and then cleaned and set aside.

[0011] In step (1), the cobalt source includes but is not limited to cobalt nitrate hexahydrate or cobalt chloride hexahydrate.

[0012] In step (1), the aluminum source includes but is not limited to aluminum nitrate nonahydrate or aluminum chloride.

[0013] In step (1), the usage ratio of the cobalt source, the aluminum source, the ammonium fluoride and the urea is 0.291-2.910 g: 0.188-1.880 g: 0.148-1.480 g: 0.601-6.010 g, and the preferred ratio is 0.291 g: 0.188 g: 0.148 g: 0.601 g.

[0014] In step (1), the temperature of the hydrothermal reaction is 80-180° C., preferably 120° C.; the reaction time is 8-24 h, preferably 12 h.

[0015] In step (2), the alkali includes but is not limited to sodium hydroxide or potassium hydroxide. The concentration of the alkali is 0.10-10 mol / L, the temperature of the alkali treatment is 5°C-100°C, and the time of the alkali treatment is 0.1-24h. Further, preferably, sodium hydroxide is used at a concentration of 5 mol / L, the temperature of the alkali treatment is 25°C, and the time of the alkali treatment is 12h.

[0016] In step (3), the noble metal solution includes but is not limited to a soluble solution of ruthenium, iridium, platinum or rhodium. The concentration of the noble metal solution is 0.010-2 mg / mL, the loading temperature is 5-80°C, and the loading time is 0.1-36 h.

[0017] The noble metal solution is preferably ruthenium trichloride; the concentration of ruthenium trichloride is 0.5 mg / mL, the loading temperature is 15° C., and the loading time is 12 h.

[0018] The present invention adopts nickel foam as a substrate, not only utilizing the three-dimensional network structure of nickel foam to grow the cobalt aluminum hydrotalcite precursor on it to increase the area for growing the catalyst in the electrocatalytic reaction, but also using nickel foam as a substrate can increase the conductivity of the catalyst. Catalysts with good conductivity are more conducive to the rapid transfer of electrons on the contact surface with the electrolyte, thereby improving the performance of the catalyst.

[0019] The alkali treatment of the present invention utilizes the amphoteric metallic properties of aluminum, effectively etches aluminum and retains cobalt metal, and the method conditions are mild and highly feasible. The metal defects after alkali treatment are evenly distributed on the entire catalyst, and the number of defects is controllable. The number of precious metals in step (3) can be controlled and evenly anchored on the catalyst, thereby improving catalytic performance. Therefore, the present invention cooperates with each other in each step, and at the same time, through the synergistic effect of the loaded precious metal and the cobalt aluminum hydrotalcite, the defect-rich cobalt aluminum hydrotalcite loaded precious metal catalyst can be used as a bifunctional electrolytic water catalyst. Since the bifunctional electrolytic water catalyst is a catalyst that can be used as a cathode and anode reaction at the same time, the catalyst composition obtained by the present invention can not only reduce the electrolytic cell pressure when the electrolytic cell decomposes water, but also reduce the complexity of the electrolytic cell assembly, simplify the actual production process, reduce production costs, and reduce energy consumption.

[0020] In a second aspect, the present invention provides an application of the defect-rich cobalt aluminum hydrotalcite-loaded precious metal catalyst as described in the first aspect, wherein the application includes use for electrolysis of water to produce hydrogen.

[0021] Preferably, the defect-rich cobalt aluminum hydrotalcite-supported noble metal catalyst is used as a bifunctional water electrolysis catalyst for hydrogen and oxygen evolution.

[0022] Preferably, when the electrolysis of water is used to produce hydrogen, the test geometric area of ​​the defect-rich cobalt-aluminum hydrotalcite-supported noble metal catalyst is 1 x 1 cm 2 .

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention provides a defect-rich cobalt aluminum hydrotalcite-loaded precious metal catalyst. The characteristics of the self-supporting cobalt aluminum hydrotalcite nanosheet array three-dimensional material in the present invention greatly increase the overall surface area of ​​the material, increase more sites for the subsequent loading of precious metals, and construct metal defect sites by alkaline etching and amphoteric metal treatment, which is beneficial to the anchoring of precious metals while reducing unstable factors such as the surface energy of the defect sites. The special combination of precious metals and carriers plays an important role in the stability of catalyst performance; the present invention jointly regulates the reaction kinetics of the water electrolysis electrode and the catalytic intrinsic activity of the catalyst through the synergistic effect of the loaded precious metal and the defect-rich cobalt aluminum hydrotalcite carrier, and regulates the electrochemical active area, thereby optimizing the overall hydrogen / oxygen evolution catalytic activity and catalytic reaction rate of the catalyst and reducing the reaction energy consumption. The electrode prepared by the catalyst of the present invention has excellent water electrolysis performance, which is helpful for application in actual working conditions.

[0025] (2) The preparation method of the material of the present invention is to synthesize a cobalt aluminum hydrotalcite precursor by a hydrothermal method, remove the amphoteric metal aluminum by alkaline etching to produce a large number of metal vacancies, and use the metal vacancies in the precursor to anchor the precious metal to increase the electrochemical active area of ​​the catalyst, thereby exposing more catalytic active sites, thereby further improving the catalytic performance while reducing costs.

[0026] (3) The instrument used in the present invention is cheap, the test method is simple, the instrument is easy to operate, and has good applicability and operability.

[0027] (4) The catalyst synthesized in the present invention exhibits excellent catalytic performance when applied to water electrolysis. With 1 mol / L KOH solution as the electrolyte, in the hydrogen evolution reaction, 10 mA·cm -2 The overpotential is as low as 57mV at a current density of 10mA·cm -2 The overpotential is as low as 370 mV at a current density of 1.5 V and can be driven as a bifunctional electrocatalyst at 10 mA cm at an electrolyzer voltage of 1.54 V. -2 Water can be decomposed by a current density of , so that the defect-rich cobalt-aluminum hydrotalcite-loaded precious metal catalyst of the present invention can be applied on an industrial scale, and can promote the development and application of electrochemical hydrogen production technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a scanning electron microscope image of the defect-rich cobalt aluminum hydrotalcite-supported noble metal catalyst described in Example 1 of the present invention;

[0029] Figure 2 This is the X-ray diffraction analysis diagram of the defect-rich cobalt aluminum hydrotalcite supported noble metal catalyst described in Example 1 of the present invention

[0030] Figure 3Polarization curves of hydrogen evolution in 1 mol / L KOH for the catalysts of Implementation 1, Comparative Example 1 and Comparative Example 2;

[0031] Figure 4 Polarization curves of oxygen evolution of catalysts in 1 mol / L KOH for implementation 1, comparative example 1 and comparative example 2;

[0032] Figure 5 Polarization curves of the catalysts of Example 1, Comparative Example 1 and Comparative Example 2 for complete water splitting in 1 mol / L KOH.

[0033] Figure 6 This is a graph of the active specific surface area of ​​the catalysts of Example 1, Comparative Example 1 and Comparative Example 2 in 1 mol / L KOH. DETAILED DESCRIPTION

[0034] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0035] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.

[0036] Example 1

[0037] This embodiment provides a method for preparing a defect-rich cobalt-aluminum hydrotalcite-supported noble metal catalyst, the preparation method comprising the following steps:

[0038] (1) Cut the nickel foam into 2.5×3 cm 2 , and then cleaned in 6mol / LHCl, anhydrous ethanol and deionized water for five minutes respectively for standby use; weigh 0.291g of cobalt nitrate hexahydrate, 0.188g of aluminum nitrate nonahydrate, 0.148g of ammonium fluoride and 0.601g of urea and dissolve them in 35mL of deionized water, and stir to form a pink transparent solution. Then, pour the pre-cleaned nickel foam and pink solution into the polytetrafluoroethylene reactor liner. Subsequently, keep the reactor at 120°C for 12h and cool it naturally to room temperature. Finally, take out the nickel foam, rinse it with deionized water three times, and dry it in a vacuum drying oven at 60°C for 12h to obtain a cobalt aluminum hydrotalcite precursor.

[0039] (2) The cobalt aluminum hydrotalcite precursor prepared in step (1) above was placed in 50 mL of 5 mol / L NaOH solution and stirred at room temperature for 12 h. After the reaction was completed, it was cleaned with deionized water and dried for standby use to obtain a defect-rich cobalt aluminum hydrotalcite carrier.

[0040] (3) 12.5 mg of ruthenium chloride was dissolved in 25 ml of deionized water, and the defect-rich cobalt aluminum hydrotalcite support prepared in step (2) was immersed in the solution, and allowed to stand at 15° C. for 12 hours to allow the defect-rich cobalt aluminum hydrotalcite support to fully adsorb Ru, and then taken out and dried in an oven to obtain the defect-rich cobalt aluminum hydrotalcite-supported noble metal catalyst.

[0041] The morphology of the defect-rich cobalt-aluminum hydrotalcite-supported noble metal catalyst described in this example is as follows: Figure 1 As shown, the nanosheets grow vertically on the surface of nickel foam, the thickness of the sheets is 60-90 nm, and the size of the sheets is 2.5-3 μm.

[0042] Figure 2 The structural diagram of the defect-rich cobalt aluminum hydrotalcite-loaded precious metal catalyst of this embodiment is shown, wherein the diffraction peaks at 11.6°, 23.2°, 34.6°, 38.8°, 60.0° and 60.9° correspond to the (003), (006), (012), (015), (110) and (0015) crystal planes of CoAl-LDHs, respectively, and no characteristic derivative peaks of the loaded metal appear.

[0043] In this embodiment, the electrocatalytic test was carried out in 1M KOH solution using a three-electrode system to test the linear sweep voltammetry to obtain a polarization curve, and the three electrodes were divided into a working electrode, a reference electrode and a counter electrode. Among them, the reference electrode was mercury / mercuric oxide, the counter electrode was a carbon rod, the working electrode was the catalyst in this embodiment, and the scan rate of the linear sweep cyclic voltammetry was 5mV / s. Figure 3 The results show that the defect-rich cobalt aluminum hydrotalcite loaded with noble metal catalysts can catalyze hydrogen evolution in alkaline solutions when the overpotential reaches 57 mV. 2 The current density, Figure 4 The catalytic oxygen evolution activity diagram in the alkaline solution of this embodiment is shown. When the overpotential reaches 300mV, it can catalyze 100mA / cm 2 When the catalysts in this embodiment are used as the cathode and anode of the dual-electrode electrolyzer system, the polarization curve of the electrolyzer system is as follows: Figure 5 shown. Figure 5 It shows that when the catalyst in this embodiment is used as the two electrodes of the electrolytic cell, only 1.54V cell voltage is required to achieve a driving current of 10mA / cm 2 The water decomposition performance of the current density. The active specific surface area of ​​the catalyst in this embodiment is as follows Figure 6As shown, the active specific surface area in alkaline solution can reach 1.67mF / cm 2 .

[0044] Example 2

[0045] (1) Cut the nickel foam into 2.5×3 cm 2 , then clean it in 6M HCl, anhydrous ethanol and deionized water for five minutes respectively and set it aside for use; weigh 0.582g of cobalt nitrate hexahydrate, 0.376g of aluminum nitrate nonahydrate, 0.296g of ammonium fluoride and 1.202g of urea and dissolve them in 70mL of deionized water, and stir them into a pink transparent solution. Then, pour the pre-cleaned nickel foam and pink solution into the polytetrafluoroethylene reactor liner. Subsequently, keep the reactor at 120°C for 12h and cool it naturally to room temperature. After that, take out the nickel foam and rinse it with deionized water three times, and dry it in a vacuum drying oven at 60°C for 12h to obtain a cobalt aluminum hydrotalcite precursor.

[0046] (2) The cobalt aluminum hydrotalcite precursor prepared in step (1) above was placed in 50 mL of 5M NaOH solution and stirred at room temperature for 12 h. After the reaction was completed, it was cleaned with deionized water and dried for standby use to obtain a defect-rich cobalt aluminum hydrotalcite carrier.

[0047] (3) 12.5 mg of ruthenium chloride was dissolved in 25 ml of deionized water, and the defect-rich cobalt aluminum hydrotalcite support prepared in step (2) was immersed in the solution, and allowed to stand at 15° C. for 12 hours to allow the defect-rich cobalt aluminum hydrotalcite support to fully adsorb Ru, and then taken out and dried in an oven to obtain the defect-rich cobalt aluminum hydrotalcite-supported noble metal catalyst.

[0048] Example 3

[0049] This embodiment provides a method for preparing a defect-rich cobalt-aluminum hydrotalcite-supported noble metal catalyst, the preparation method comprising the following steps:

[0050] (1) Cut the nickel foam into 2.5×3 cm 2 , and then cleaned in 6M HCl, anhydrous ethanol and deionized water for five minutes respectively for standby use; weigh 0.291g of cobalt nitrate hexahydrate, 0.188g of aluminum nitrate nonahydrate, 0.148g of ammonium fluoride and 0.601g of urea and dissolve them in 35mL of deionized water, stirring into a pink transparent solution. Then, pour the pre-cleaned nickel foam and pink solution into the polytetrafluoroethylene reactor liner. Subsequently, keep the reactor at 120°C for 12h and cool it naturally to room temperature. Finally, take out the nickel foam, rinse it with deionized water three times, and dry it in a vacuum drying oven at 60°C for 12h to obtain a cobalt aluminum hydrotalcite precursor.

[0051] (2) The cobalt aluminum hydrotalcite precursor prepared in step (1) above was placed in 50 mL of 6M NaOH solution and stirred at room temperature for 12 h. After the reaction was completed, it was cleaned with deionized water and dried for standby use to obtain a defect-rich cobalt aluminum hydrotalcite carrier.

[0052] (3) 12.5 mg of ruthenium chloride was dissolved in 25 ml of deionized water, and the defect-rich cobalt aluminum hydrotalcite support prepared in step (2) was immersed in the solution, and allowed to stand at 15° C. for 12 hours to allow the defect-rich cobalt aluminum hydrotalcite support to fully adsorb Ru, and then taken out and dried in an oven to obtain the defect-rich cobalt aluminum hydrotalcite-supported noble metal catalyst.

[0053] Example 4

[0054] This embodiment provides a method for preparing a defect-rich cobalt-aluminum hydrotalcite-supported noble metal catalyst, the preparation method comprising the following steps:

[0055] (1) Cut the nickel foam into 2.5×3 cm 2 , and then cleaned in 6M HCl, anhydrous ethanol and deionized water for five minutes respectively for standby use; weigh 0.291g of cobalt nitrate hexahydrate, 0.188g of aluminum nitrate nonahydrate, 0.148g of ammonium fluoride and 0.601g of urea and dissolve them in 35mL of deionized water, stirring into a pink transparent solution. Then, pour the pre-cleaned nickel foam and pink solution into the polytetrafluoroethylene reactor liner. Subsequently, keep the reactor at 120°C for 12h and cool it naturally to room temperature. Finally, take out the nickel foam, rinse it with deionized water three times, and dry it in a vacuum drying oven at 60°C for 12h to obtain a cobalt aluminum hydrotalcite precursor.

[0056] (2) The cobalt aluminum hydrotalcite precursor prepared in step (1) above was placed in 50 mL of 6M NaOH solution and stirred at room temperature for 12 h. After the reaction was completed, it was cleaned with deionized water and dried for standby use to obtain a defect-rich cobalt aluminum hydrotalcite carrier.

[0057] (3) 7.5 mg of ruthenium chloride was dissolved in 25 ml of deionized water, and the defect-rich cobalt aluminum hydrotalcite support prepared in step (2) was immersed in the solution, and allowed to stand at 15° C. for 12 hours to allow the defect-rich cobalt aluminum hydrotalcite support to fully adsorb Ru, and then taken out and dried in an oven to obtain the defect-rich cobalt aluminum hydrotalcite-supported noble metal catalyst.

[0058] Comparative Example 1

[0059] This comparative example provides a method for preparing a catalyst. The preparation method is step (1) in Example 1, and the obtained catalyst is a cobalt aluminum hydrotalcite precursor.

[0060] Figure 2It is shown that the diffraction peaks of the catalyst in Comparative Example 1 correspond to the diffraction peaks of pure cobalt aluminum hydrotalcite, which are 11.6°, 23.2°, 34.6°, 38.8°, 60.0° and 60.9°, respectively, corresponding to the (003), (006), (012), (015), (110) and (0015) crystal planes of CoAl-LDHs. The electrocatalytic test was carried out under the same conditions as in Example 1, wherein the cobalt aluminum hydrotalcite in this comparative example was used as the working electrode. Figure 3 The results show that the hydrogen evolution performance of cobalt aluminum hydrotalcite in alkaline solution in comparative example 1 is 10 mA / cm2 only when the overpotential reaches 237 mV. 2 The current density, Figure 4 The oxygen evolution activity diagram of the cobalt aluminum hydrotalcite in the alkaline solution in comparative example 1 is shown. When the overpotential reaches 360mV, it can catalyze 100mA / cm 2 When the cobalt-aluminum hydrotalcite in Example 1 is used as the cathode and anode of the dual-electrode electrolytic cell system, the polarization curve of the electrolytic cell system is as follows: Figure 5 shown. Figure 5 It shows that when the catalyst in this comparative example is used as the two electrodes of the electrolytic cell, a cell voltage of 1.76V is required to achieve a driving current of 10mA / cm 2 The water decomposition performance of the current density. The active specific surface area of ​​the catalyst in this comparative example is as follows Figure 6 As shown, the active specific surface area in alkaline solution is only 0.33mF / cm 2 , which is much lower than the specific surface area of ​​the catalyst in Example 1.

[0061] Comparative Example 2 Preparation of defect-rich cobalt aluminum hydrotalcite precursor

[0062] This comparative example provides a method for preparing a catalyst. The preparation method is steps (1) and (2) in Example 1, and a defect-rich cobalt aluminum hydrotalcite carrier is obtained.

[0063] Figure 2 It is shown that the diffraction peaks of the defect-rich cobalt aluminum hydrotalcite in Comparative Example 2 correspond to the diffraction peaks of pure cobalt aluminum hydrotalcite, which are 11.6°, 23.2°, 34.6°, 38.8°, 60.0° and 60.9°, respectively, corresponding to the (003), (006), (012), (015), (110) and (0015) crystal planes of CoAl-LDHs. It is shown that the structure of the cobalt aluminum hydrotalcite is not significantly changed after etching. The electrocatalytic test is carried out under the same conditions as those used in Example 1, wherein the working electrode uses the cobalt aluminum hydrotalcite in this comparative example. Figure 3 The hydrogen evolution performance of the defect-rich cobalt aluminum hydrotalcite in the alkaline solution of Comparative Example 2 is shown. When the overpotential reaches 222 mV, it can catalyze 10 mA / cm 2 The current density, Figure 4The oxygen evolution activity diagram of the defect-rich cobalt aluminum hydrotalcite in the alkaline solution in comparative example 2 is shown. When the overpotential reaches 350mV, it can catalyze 100mA / cm 2 When the defect-rich cobalt-aluminum hydrotalcite in Ratio 2 is used as the cathode and anode of the dual-electrode electrolytic cell system, the polarization curve of the electrolytic cell system is as follows: Figure 5 shown. Figure 5 It shows that when the catalyst in this comparative example 2 is used as the two electrodes of the electrolytic cell, a cell voltage of 1.72V is required to achieve a driving current of 10mA / cm 2 The water decomposition performance of the current density. The active specific surface area of ​​the catalyst in this comparative example is as follows Figure 6 As shown, the active specific surface area in alkaline solution is only 0.473mF / cm 2 , which is also lower than the specific surface area of ​​the catalyst in Example 1.

[0064] contrast Figures 1 to 6 It can be seen that:

[0065] The catalyst provided by the present invention does not change the crystal structure of the original catalyst after alkali treatment and precious metal loading, and has a smaller overpotential for hydrogen evolution and oxygen evolution; it can be seen from Example 1, Comparative Example 1 and Comparative Example 2 that the catalyst obtained by the present invention has better performance and can be used as a bifunctional catalyst.

[0066] In summary, the present invention provides a defect-rich cobalt aluminum hydrotalcite-loaded noble metal catalyst and its preparation method and application. The preparation method can produce a catalyst with a large electrochemically active specific surface area through a simple process. The loading of noble metals can increase a large number of catalytic active sites and improve the intrinsic activity of the catalyst. It can also be used as a dual-function water electrolysis catalyst for hydrogen and oxygen evolution.

[0067] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A method for preparing a defect-rich cobalt-aluminum hydrotalcite-supported noble metal catalyst, characterized in that: The steps include: (1) pre-treating the nickel foam to remove the oxide on its surface, and then placing the pre-treated nickel foam in a mixed solution containing a certain proportion of a cobalt source, an aluminum source, ammonium fluoride, urea and water, and growing a cobalt aluminum hydrotalcite precursor on the nickel foam substrate through a hydrothermal reaction; (2) further treating the cobalt aluminum hydrotalcite precursor obtained in step (1) with alkali etching and then drying to obtain a defect-rich cobalt aluminum hydrotalcite carrier; (3) Immersing the defect-rich cobalt aluminum hydrotalcite precursor obtained in step (2) into a noble metal solution, taking out the sample after the immersion is completed and drying it, and finally obtaining the defect-rich cobalt aluminum hydrotalcite-loaded noble metal catalyst.

2. The preparation method according to claim 1, characterized in that In step (1), the specific process of the nickel foam pretreatment is as follows: first, the nickel foam is cut into (1-3)×(1-3) cm 2 The size of the nickel foam was then ultrasonically cleaned in an acidic solution with a pH value less than 4, anhydrous ethanol and deionized water for 5 minutes to remove the surface oxide, and then cleaned and set aside.

3. The preparation method according to claim 1, characterized in that: In step (1), the cobalt source includes but is not limited to cobalt nitrate hexahydrate or cobalt chloride hexahydrate; the aluminum source includes but is not limited to aluminum nitrate nonahydrate or aluminum chloride.

4. The preparation method according to claim 1, characterized in that: In step (1), the usage ratio of the cobalt source, the aluminum source, the ammonium fluoride and the urea is 0.291-2.910 g: 0.188-1.880 g: 0.148-1.480 g: 0.601-6.010 g; the temperature of the hydrothermal reaction is 80-180° C., and the reaction time is 8-24 h.

5. The preparation method according to claim 4, characterized in that: In step (1), the usage ratio of the cobalt source, the aluminum source, the ammonium fluoride and the urea is 0.291 g: 0.188 g: 0.148 g: 0.601 g; the temperature of the hydrothermal reaction is 120° C.; and the reaction time is 12 h.

6. The preparation method according to claim 1, characterized in that: In step (2), the alkali includes but is not limited to sodium hydroxide or potassium hydroxide, the concentration of the alkali is 0.10-10 mol / L, the temperature of the alkali treatment is 5° C.-100° C., and the time of the alkali treatment is 0.1-24 h.

7. The preparation method according to claim 6, characterized in that: In step (2), the alkali is sodium hydroxide, the concentration of the alkali is 5 mol / L, the temperature of the alkali treatment is 25° C., and the time of the alkali treatment is 12 h.

8. The preparation method according to claim 1, characterized in that: In step (3), the noble metal solution includes but is not limited to a soluble solution of ruthenium, iridium, platinum or rhodium, the concentration of the noble metal solution is 0.010-2 mg / mL, the loading temperature is 5-80°C, and the loading time is 0.1-36h.

9. The preparation method according to claim 8, characterized in that: In step (3), the noble metal solution is preferably ruthenium trichloride; the concentration of ruthenium trichloride is 0.5 mg / mL, the loading temperature is 15° C., and the loading time is 12 h.

10. Use of the defect-rich cobalt-aluminum hydrotalcite-supported noble metal catalyst prepared by the preparation method according to any one of claims 1 to 9 for producing hydrogen by electrolysis of water.

Citation Information

Cited By

  • Preparation method of ultrathin LDH confinement ruthenium monatomic catalyst for defect engineering regulation and control and application of ultrathin LDH confinement ruthenium monatomic catalyst in photocatalytic CO2 reduction

    CN121198317A